Brain morphometry in hepatic Wilson disease patients - Rahimi, Parya; Mareček, Stanislav; Brůha, Radan; Dezortová, Monika; Sojka, Petr; Hájek, Milan; Skowrońska, Marta; Smoliński, Łukasz; Urbánek, Petr; Litwin, Tomasz; Dušek, Petr (Journal of inherited metabolic disease, 2025)
Wilson disease (WD) primarily presents with hepatic and neurological symptoms. While hepatic symptoms typically precede the neurological manifestations, copper accumulates in the brain already in this patient group and leads to subclinical brain MRI abnormalities including T2 hyperintensities and atrophy. This study aimed to assess brain morphological changes in mild hepatic WD. WD patients without a history of neurologic symptoms and decompensated cirrhosis and control participants underwent brain MRI at 3T scanner including high-resolution T1-weighted images. A volumetric evaluation was conducted on the following brain regions: nucleus accumbens, caudate, pallidum, putamen, thalamus, amygdala, hippocampus, midbrain, pons, cerebellar gray matter, white matter (WM), and superior peduncle, using Freesurfer v7 software. Whole-brain analyses using voxel- and surface-based morphometry were performed using SPM12. Statistical comparisons utilized a general linear model adjusted for total intracranial volume, age, and sex. Twenty-six WD patients with mild hepatic form (30 ± 9 years [mean age ± SD]); 11 women; mean treatment duration 13 ± 12 (range 0-42) years and 28 healthy controls (33 ± 9 years; 15 women) were evaluated. Volumetric analysis revealed a significantly smaller pons volume and a trend for smaller midbrain and cerebellar WM in WD patients compared to controls. Whole-brain analysis revealed regions of reduced volume in the pons, cerebellar, and lobar WM in the WD group. No significant differences in gray matter density or cortical thickness were found. Myelin or WM in general seems vulnerable to low-level copper toxicity, with WM volume loss showing promise as a marker for assessing brain involvement in early WD stages.
Keywords: Liver; MRI; játra; morphometry; hepatolentikulární degenerace; Wilson disease; white matter; brainstem; bílá hmota; Middle Aged; mužské pohlaví; Gray Matter; studie případů a kontrol; mozek; Adult; mladý dospělý; brain atrophy; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Young Adult; hepatic; ženské pohlaví; šedá hmota; Humans; Hepatolenticular Degeneration; lidé středního věku; White Matter; Case-Control Studies; dospělí; Female; lidé; Male